Conceptualization of a Parasympathetic Endocrine System - Gorky, Jonathan; Schwaber, James (Frontiers in Neuroscience, 2019)
We here propose a parasympathetic endocrine system (PES) comprised of circulating peptides released from secretory cells in the gut, significantly modulated by vagal projections from the dorsal motor nucleus of the vagus (DMV). While most of these gut peptides mediate well-described satiety and digestive effects that increase parasympathetic control of digestion (Lee et al., 1994; Gutzwiller et al., 1999; Klok et al., 2007), they also have actions that are far-reaching and increase parasympathetic signaling broadly throughout the body. The actions beyond satiety that peptides like somatostatin, cholecystokinin, glucagon-like peptide 1, and vasoactive intestinal peptide have been well-examined, but not in a systematic way. Consideration has been given to the idea that these and other gut-derived peptides are part of an endocrine system has been partially considered (Rehfeld, 2012; Drucker, 2016), but that it is coordinated through parasympathetic control and may act to increase the actions of parasympathetic projections has not been formalized before. Here only gut-derived hormones are included although there are potentially other parasympathetically mediated factors released from other sites like lung and liver (Drucker, 2016). The case for the existence of the PES with the DMV as its integrative controller will be made through examination of an anatomical substrate and evidence of physiological control mechanisms as well as direct examples of PES antagonism of sympathetic signaling in mammals, including humans. The implications for this conceptual understanding of a PES reframe diseases like metabolic syndrome and may help underscore the role of the autonomic nervous system in the associated symptoms.